Genomics reveal population structure, evolutionary history, and signatures of selection in the northern bottlenose whale, Hyperoodon ampullatus. Issue 19 (23rd August 2022) - de Greef, Evelien; Einfeldt, Anthony L.; Miller, Patrick J. O.; Ferguson, Steven H.; Garroway, Colin J.; Lefort, Kyle J.; Paterson, Ian G.; Bentzen, Paul; Feyrer, Laura J.
Abstract: Information on wildlife population structure, demographic history, and adaptations are fundamental to understanding species evolution and informing conservation strategies. To study this ecological context for a cetacean of conservation concern, we conducted the first genomic assessment of the northern bottlenose whale, Hyperoodon ampullatus, using whole‐genome resequencing data ( n = 37) from five regions across the North Atlantic Ocean. We found a range‐wide pattern of isolation‐by‐distance with a genetic subdivision distinguishing three subgroups: the Scotian Shelf, western North Atlantic, and Jan Mayen regions. Signals of elevated levels of inbreeding in the Endangered Scotian Shelf population indicate this population may be more vulnerable than the other two subgroups. In addition to signatures of inbreeding, evidence of local adaptation in the Scotian Shelf was detected across the genome. We found a long‐term decline in effective population size for the species, which poses risks to their genetic diversity and may be exacerbated by the isolating effects of population subdivision. Protecting important habitat and migratory corridors should be prioritized to rebuild population sizes that were diminished by commercial whaling, strengthen gene flow, and ensure animals can move across regions in response to environmental changes.